MoS2 / MoN / C conductive agent, preparation method thereof and application of MoS2 / MoN / C conductive agent in sulfide all-solid-state battery
By preparing MoS2/MoN/C conductive agent, the problem of interfacial side reactions of carbon materials in all-solid-state batteries was solved, higher electronic conductivity and ion mobility were achieved, and the stability and cycle performance of the battery were improved.
Patent Information
- Application Number
- CN202511232975.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2025-10-03
- Estimated Expiration
- 2045-09-01
AI Technical Summary
Existing carbon materials as conductive agents cannot effectively inhibit the chemical/electrochemical side reactions between sulfide electrolytes and cathode materials in all-solid-state batteries, resulting in poor interface stability and affecting battery performance.
The preparation method of MoS2/MoN/C conductive agent is adopted. The MoS2/MoN/C conductive agent is formed by impregnation and pyrolysis reaction of formaldehyde-melamine polymer microspheres, molybdenum salt and ammonia water. The method reduces the surface defect density of the material, promotes the migration of Li ions and electrons, avoids direct contact between the carbon material and the conductive agent, and inhibits interfacial side reactions.
The MoS2/MoN/C conductive agent exhibits excellent electronic conductivity and ion mobility in sulfide all-solid-state batteries, improves the stability and cycle performance of the battery, and inhibits the occurrence of interfacial side reactions.
Smart Images

Figure CN120749167A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a MoS2 / MoN / C conductive agent, a preparation method thereof, and application in sulfide all-solid-state batteries. Background Art
[0002] All-solid-state lithium-ion batteries are considered to be one of the promising solutions to replace lithium-ion batteries due to their high safety and high energy density. In order to further improve the cycle stability of all-solid-state batteries, constructing a composite positive electrode composed mainly of active materials, sulfide electrolytes and carbon additives has become the mainstream solution. However, due to the limited chemical / electrochemical stability of sulfide electrolytes, side reactions will occur at the interface, thereby deteriorating battery performance. It is worth noting that carbon additives that improve the electronic conductivity of positive electrode materials will promote the further decomposition of sulfide electrolytes. Studies have shown that these decomposition products, especially sulfites, will block the lithium ion or electron conduction channels in the positive electrode, resulting in contact loss and reducing battery capacity.
[0003] Currently, most research related to carbon materials focuses on their morphology, particle size, specific surface area, etc. However, these methods are still unable to effectively suppress chemical / electrochemical side reactions at the interface to improve interface stability. Summary of the Invention
[0004] In light of this, the present invention provides a MoS2 / MoN / C conductive agent, a preparation method thereof, and its use in sulfide all-solid-state batteries. The MoS2 / MoN / C conductive agent provided by the present invention does not induce chemical or electrochemical side reactions between the sulfide solid electrolyte and the cathode material, and exhibits excellent stability.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A method for preparing a MoS2 / MoN / C conductive agent comprises the following steps: Formaldehyde, melamine, an emulsifier, an emulsifier aid, and a first solvent are mixed for polycondensation reaction to obtain formaldehyde-melamine polymer microspheres; the emulsifier comprises a first emulsifier and a second emulsifier; the first emulsifier is a Span series emulsifier, and the second emulsifier is one or more of a Tween series emulsifier and an OP series emulsifier; the molar ratio of formaldehyde to melamine is greater than or equal to 4:1; The formaldehyde-melamine polymer microspheres, ammonia water, a molybdenum salt solution and a second solvent are mixed and impregnated to obtain a polymer precursor; the concentration of the molybdenum salt solution is greater than or equal to 0.01 mol / L; The polymer precursor and thiourea are subjected to a pyrolysis reaction to obtain a MoS2 / MoN / C conductive agent; the temperature of the pyrolysis reaction is greater than or equal to 600°C, and the time is greater than or equal to 5 hours.
[0006] Preferably, the co-emulsifier is alcohol; the first solvent is a water-in-oil emulsion; the volume ratio of the continuous oil phase to water in the water-in-oil emulsion is (6-12):1; The ratio of the mass of the emulsifier to the volume of the first solvent is 5-15 g:100 mL; the volume ratio of the co-emulsifier to the first solvent is 2-10:100; The molar ratio of the formaldehyde to melamine is (4-12):1; the usage ratio of the melamine to the first solvent is 0.01-0.1 mol:100 mL.
[0007] Preferably, the temperature of the polycondensation reaction is 40-60° C., and the reaction time is 6-12 hours.
[0008] Preferably, the molybdenum salt in the molybdenum salt solution includes (NH4)2MoO4 and C8H 12 One or two of Mo2O8; the concentration of the molybdenum salt solution is 0.01~0.1mol / L; the second solvent is water; The volume ratio of the formaldehyde-melamine polymer microspheres to the second solvent is 5-20 g:100 mL; the volume ratio of the molybdenum salt solution to the second solvent is 30-60:100; the volume fraction of the ammonia water is 4-6%; and the volume ratio of the ammonia water to the second solvent is 5-20:100.
[0009] Preferably, the immersion temperature is 25-35° C. and the immersion time is 6-24 hours.
[0010] Preferably, the mass ratio of the polymer precursor to thiourea is 100:5-50; the temperature of the pyrolysis reaction is 600-1000° C., the time is 5-10 h, and the pyrolysis reaction is carried out in a protective atmosphere.
[0011] The present invention also provides a MoS2 / MoN / C conductive agent prepared by the preparation method described in the above scheme, wherein the mass fraction of MoS2 in the MoS2 / MoN / C conductive agent is 3~5%, the mass fraction of MoN is 8~10%, and the mass fraction of C is 85~89%.
[0012] The present invention also provides the use of the MoS2 / MoN / C conductive agent described in the above scheme in a sulfide all-solid-state battery.
[0013] The present invention also provides a positive electrode material, comprising the MoS2 / MoN / C conductive agent, sulfide electrolyte and active material described in the above scheme.
[0014] The present invention also provides a sulfide all-solid-state battery, comprising a positive electrode, a negative electrode and a sulfide solid electrolyte, wherein the positive electrode is the positive electrode material described in the above scheme.
[0015] The present invention provides a preparation method of a MoS2 / MoN / C conductive agent, comprising the following steps: mixing formaldehyde, melamine, an emulsifier, an emulsifier aid and a first solvent for polycondensation reaction to obtain formaldehyde-melamine polymer microspheres; the emulsifier comprises a first emulsifier and a second emulsifier; the first emulsifier is a Span series emulsifier, and the second emulsifier is one or more of a Tween series emulsifier and an OP series emulsifier; the molar ratio of the formaldehyde to melamine is greater than or equal to 4:1; the formaldehyde-melamine polymer microspheres, ammonia water, a molybdenum salt solution and a second solvent are mixed and impregnated to obtain a polymer precursor; the concentration of the molybdenum salt solution is greater than or equal to 0.01 mol / L; the polymer precursor and thiourea are subjected to a pyrolysis reaction to obtain a MoS2 / MoN / C conductive agent; the temperature of the pyrolysis reaction is greater than or equal to 600°C, and the time is greater than or equal to 5 hours. The present invention first prepares formaldehyde-melamine polymer microspheres, then allows the formaldehyde-melamine microspheres to adsorb molybdenum salt and ammonia water by impregnation to obtain a polymer precursor, and finally causes the polymer precursor to lose H and O elements to form C through a thermal decomposition reaction between the polymer precursor and thiourea. The molybdenum salt reacts under conditions of sufficient nitrogen source to form MoN. In addition, the molybdenum salt forms MoS2 at the interface with thiourea, thereby obtaining a MoS2 / MoN / C conductive agent. The doping of the Mo element can effectively reduce the anti-occupying defects generated in the material during the preparation process, thereby reducing the defect density on the surface of the material. In addition, the molybdenum sulfide material, as an excellent dual-carrier conductor (with high ion mobility and electronic conductivity), is not only beneficial to the migration of Li ions and electrons in the positive electrode material, but also prevents direct contact between the carbon material and the conductive agent to a certain extent, thereby reducing interfacial side reactions. Compared with traditional conductive agents, the MoS2 / MoN / C conductive agent prepared by the present invention will not induce chemical / electrochemical side reactions between the sulfide solid electrolyte and the positive electrode material, has excellent electronic conductivity and ion mobility, and has excellent stability, which can promote the development of sulfide electrolyte all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the equivalent circuit diagram of the sulfide all-solid-state battery; Figure 2 This is the XPS spectrum of the positive electrode material of the sulfide all-solid-state battery containing conductive carbon black and the MoS2 / MoN / C conductive agent in Example 1 after 100 cycles, where a is conductive carbon black and b is MoS2 / MoN / C conductive agent. DETAILED DESCRIPTION
[0017] The present invention provides a method for preparing a MoS2 / MoN / C conductive agent, comprising the following steps: Formaldehyde, melamine, an emulsifier, an emulsifier aid, and a first solvent are mixed for polycondensation reaction to obtain formaldehyde-melamine polymer microspheres; the emulsifier comprises a first emulsifier and a second emulsifier; the first emulsifier is a Span series emulsifier, and the second emulsifier is one or more of a Tween series emulsifier and an OP series emulsifier; the molar ratio of formaldehyde to melamine is greater than or equal to 4:1; The formaldehyde-melamine polymer microspheres, ammonia water, a molybdenum salt solution and a second solvent are mixed and impregnated to obtain a polymer precursor; the concentration of the molybdenum salt solution is greater than or equal to 0.01 mol / L; The polymer precursor and thiourea are subjected to a pyrolysis reaction to obtain a MoS2 / MoN / C conductive agent; the temperature of the pyrolysis reaction is greater than or equal to 600°C, and the time is greater than or equal to 5 hours.
[0018] The invention mixes formaldehyde, melamine, an emulsifier, an auxiliary emulsifier and a first solvent to carry out polycondensation reaction to obtain formaldehyde-melamine polymer microspheres. In the present invention, the emulsifier includes a first emulsifier and a second emulsifier; the first emulsifier is a Span series emulsifier, and the second emulsifier is one or more of a Tween series emulsifier and an OP series emulsifier; the Span series emulsifier preferably includes one or more of Span-85, Span-80, Span-65, Span-60, Span-40 and Span-20; the Tween series emulsifier preferably includes one or more of Tween-20, Tween-40, Tween-60 and Tween-80; the OP series emulsifier preferably includes one or more of OP-4, OP-7, OP-9, OP-10, OP-13, OP-15, OP-20, OP-30, OP-40 and OP-50; the present invention compounds the Span series emulsifier with the Tween series emulsifier, or compounds the Span series emulsifier with the OP series emulsifier, which is beneficial to improving the stability of the oil-water interface.
[0019] In the present invention, the co-emulsifier is preferably an alcohol; the alcohol preferably includes one or more of n-butanol, n-hexanol and isobutanol; the introduction of the co-emulsifier is beneficial to reducing the diameter of the droplets in the oil-in-water emulsion and is beneficial to the formation of micro-nano polymer microspheres.
[0020] In the present invention, the first solvent is preferably a water-in-oil emulsion; the volume ratio of the continuous oil phase to water in the water-in-oil emulsion is preferably (6-12):1, specifically 6:1, 8:1, 9:1, 10:1, or 12:1; the continuous phase oil is preferably one or both of white oil and kerosene, and the water is preferably deionized water. The present invention limits the volume ratio of the continuous phase oil to water to the above range to form a water-in-oil emulsion with good results. If the volume ratio of the continuous phase oil to water is too low, for example, a ratio of 1:1, it is difficult to form a water-in-oil emulsion.
[0021] In the present invention, the ratio of the mass of the emulsifier to the volume of the first solvent is preferably 5-15 g:100 mL, more preferably 8-15 g:100 mL; the volume ratio of the co-emulsifier to the first solvent is preferably 2-10:100, more preferably 2.5-6:100.
[0022] In the present invention, the molar ratio of formaldehyde to melamine is greater than or equal to 4:1, preferably (4-12):1, more preferably (6-12):1; the usage ratio of melamine to the first solvent is preferably 0.01-0.1 mol:100 mL, more preferably 0.05-0.1 mol:100 mL.
[0023] In the present invention, the temperature of the polycondensation reaction is preferably 40-60° C., more preferably 45-55° C., and the time of the polycondensation reaction is preferably 6-12 h, more preferably 8-10 h; the polycondensation reaction is preferably carried out under nitrogen protection.
[0024] In a specific embodiment of the present invention, a first solvent, an emulsifier, and a co-emulsifier are preferably added sequentially to a three-necked round-bottom flask equipped with a stirring rod, a thermometer, and a nitrogen inlet tube. After stirring at room temperature for 20 to 60 minutes, formaldehyde and melamine are added sequentially, and the temperature is then raised to the polycondensation reaction temperature for reaction. After the reaction is completed, the present invention preferably centrifuges the resulting product liquid, washes the resulting solid product, and vacuum-dries it to obtain formaldehyde-melamine polymer microspheres; the formaldehyde-melamine polymer microspheres have a size of micro-nanoscale, specifically 2 to 5 μm.
[0025] After obtaining the formaldehyde-melamine polymer microspheres, the present invention mixes the formaldehyde-melamine polymer microspheres, ammonia water, a molybdenum salt solution, and a second solvent for impregnation to obtain a polymer precursor. In the present invention, the second solvent is preferably water, specifically deionized water. The concentration of the molybdenum salt solution is greater than or equal to 0.01 mol / L, preferably 0.01 to 0.1 mol / L, and more preferably 0.03 to 0.08 mol / L. The molybdenum salt in the molybdenum salt solution preferably includes (NH4)2MoO4 (ammonium molybdate) and C8H 12One or two of Mo2O8 (molybdenum (II) acetate dimer); the volume ratio of the molybdenum salt solution and the second solvent is preferably 30~60:100, more preferably 45~60:100; the volume ratio of the formaldehyde-melamine polymer microspheres and the second solvent is preferably 5~20g:100mL, more preferably 8~15g:100mL; the volume fraction of the ammonia water is preferably 4~6%, more preferably 5%; the volume ratio of the ammonia water and the second solvent is preferably 5~20:100.
[0026] In the present invention, the impregnation temperature is preferably 25-35°C, specifically 30°C, and the impregnation time is preferably 6-24h, specifically 6h, 8h, 12h or 24h; the impregnation is preferably carried out under static conditions; during the impregnation process, the molybdenum salt and ammonia water are adsorbed into the formaldehyde-melamine polymer microspheres.
[0027] After the impregnation is completed, the present invention preferably freeze-dries the impregnated product. The freeze-drying temperature is preferably -60°C, the pressure is preferably 12 Pa, and the drying time is preferably 12 to 24 hours.
[0028] After obtaining the polymer precursor, the present invention conducts a pyrolysis reaction between the polymer precursor and thiourea to obtain a MoS2 / MoN / C conductive agent. In the present invention, the mass ratio of the polymer precursor to thiourea is preferably 100:5~50, more preferably 100:30~50; the temperature of the pyrolysis reaction is greater than or equal to 600°C, preferably 600~1000°C, more preferably 800~1000°C, and the time of the pyrolysis reaction is greater than or equal to 5h, preferably 5~10h, more preferably 8~10h; the pyrolysis reaction is preferably carried out under a protective atmosphere, preferably Ar; the pyrolysis reaction is preferably carried out in a tube furnace. During the pyrolysis reaction, the polymer precursor loses H and O elements to form C, and the metal molybdenum salt reacts under sufficient nitrogen source conditions to form MoN. In addition, the metal molybdenum salt forms MoS2 at the interface with thiourea to obtain a MoS2 / MoN / C conductive agent.
[0029] The present invention also provides a MoS2 / MoN / C conductive agent prepared by the preparation method described in the above scheme, wherein the mass fraction of MoS2 in the MoS2 / MoN / C conductive agent is 3~5%, the mass fraction of MoN is 8~10%, and the mass fraction of C is 85~89%.
[0030] In the present invention, the average particle size of the MoS2 / MoN / C conductive agent is preferably 800~6500nm, more preferably 800~1600nm.
[0031] The present invention also provides the use of the MoS2 / MoN / C conductive agent described in the above scheme in sulfide all-solid-state batteries. The MoS2 / MoN / C conductive agent prepared by the present invention does not induce chemical or electrochemical side reactions in the sulfide solid electrolyte cathode material, exhibits excellent electronic conductivity and ion mobility, and has excellent stability, showing broad application prospects in sulfide all-solid-state batteries.
[0032] The present invention also provides a positive electrode material, comprising the MoS2 / MoN / C conductive agent, sulfide electrolyte and active material described in the above scheme; the present invention has no special requirements for the sulfide electrolyte and active material, and those familiar to those skilled in the art can be used; in a specific embodiment of the present invention, the sulfide electrolyte can be LPSC, and the active material can be lithium cobalt oxide (LCO); the weight ratio of the MoS2 / MoN / C conductive agent, sulfide electrolyte and active material is preferably 8:22:70.
[0033] The present invention also provides a sulfide all-solid-state battery, comprising a positive electrode, a negative electrode, and a sulfide solid electrolyte, wherein the positive electrode is the positive electrode material described in the above embodiment. The present invention has no special requirements for the specific structure and assembly method of the sulfide all-solid-state battery, and methods familiar to those skilled in the art can be used. Figure 1 This is the equivalent circuit diagram of the sulfide all-solid-state battery.
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0035] Example 1 (1) In a three-necked round-bottom flask equipped with a stirring rod, a thermometer, and a nitrogen inlet tube, 20 mL of deionized water, 27.5 g of Span60, 5.5 g of Tween20, and 10 mL of n-butanol were added to 200 mL of white oil in sequence. The mixture was stirred at room temperature for 60 min. 2.64 mol of formaldehyde and 0.22 mol of melamine were then added in sequence. The temperature was raised to 60°C and the reaction was continued for 10 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum-dried to obtain formaldehyde-melamine polymer microspheres.
[0036] (2) 15 g of formaldehyde-melamine polymer microspheres, 20 mL of 5 wt% ammonia water, and 60 mL of 0.08 mol / L (NH4)2MoO4 solution were added to 100 mL of deionized water in sequence, and the mixture was allowed to stand at 35 °C for 24 h. The mixture was then freeze-dried (-60 °C, 12 Pa) for 24 h to obtain a polymer precursor.
[0037] (3) In a tubular furnace filled with Ar atmosphere, 50 g of polymer precursor was uniformly mixed with 25 g of thiourea, and the temperature was raised to 1000 °C for pyrolysis for 10 h to finally obtain MoS2 / MoN / C conductive agent (the mass fraction of MoS2 was 3.5%, the mass fraction of MoN was 8.5%, and the mass fraction of C was 88.0%).
[0038] The obtained product was named Conductive Agent-1, and had an average particle size of 842 nm.
[0039] Example 2 (1) In a three-necked round-bottom flask equipped with a stirring rod, thermometer, and nitrogen inlet tube, 20 mL of deionized water, 12.3 g of Span85, 2.1 g of OP-10, and 5 mL of n-hexanol were added to 160 mL of kerosene in sequence. The mixture was stirred at room temperature for 20 min. 0.54 mol of formaldehyde and 0.09 mol of melamine were then added in sequence. The temperature was raised to 40°C and the reaction was continued for 8 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum-dried to obtain formaldehyde-melamine polymer microspheres.
[0040] (2) Add 16 g of formaldehyde-melamine polymer microspheres, 10 mL of ammonia water and 90 mL of 0.03 mol / L C8H 12 The Mo2O8 solution was allowed to stand at 25 °C for 6 h and then freeze-dried (-60 °C, 12 Pa) for 12 h to finally obtain the polymer precursor.
[0041] (3) In a tubular furnace filled with Ar atmosphere, 50 g of polymer precursor was uniformly mixed with 15 g of thiourea, and the temperature was raised to 800 °C for pyrolysis for 8 h to finally obtain MoS2 / MoN / C conductive agent (the mass fraction of MoS2 was 4.5%, the mass fraction of MoN was 9.2%, and the mass fraction of C was 86.3%).
[0042] The obtained product was named conductive agent-2, and the average particle size was 1549 nm.
[0043] Example 3 (1) In a three-necked round-bottom flask equipped with a stirring rod, a thermometer, and a nitrogen inlet tube, 20 mL of deionized water, 8.0 g of Span60, 2.0 g of OP-40, and 8 mL of isobutanol were added to 180 mL of kerosene in sequence. The mixture was stirred at room temperature for 40 min. 1.28 mol of formaldehyde and 0.16 mol of melamine were then added in sequence. The temperature was raised to 50°C and the reaction was continued for 9 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum-dried to obtain formaldehyde-melamine polymer microspheres.
[0044] (2) 24 g of formaldehyde-melamine polymer microspheres, 20 mL of ammonia water, and 100 mL of 0.05 mol / L (NH4)2MoO4 solution were added to 200 mL of deionized water in sequence, and the mixture was allowed to stand at 30 °C for 12 h. The mixture was then freeze-dried (-60 °C, 12 Pa) for 18 h to obtain a polymer precursor.
[0045] (3) In a tubular furnace filled with Ar atmosphere, 100 g of polymer precursor was uniformly mixed with 40 g of thiourea, and the temperature was raised to 900 °C for pyrolysis for 9 h to finally obtain MoS2 / MoN / C conductive agent (the mass fraction of MoS2 was 4.8%, the mass fraction of MoN was 9.8%, and the mass fraction of C was 85.4%).
[0046] The obtained product was named conductive agent-3, and the average particle size was 1054 nm.
[0047] Example 4 (1) In a three-necked round-bottom flask equipped with a stirring rod, a thermometer, and a nitrogen inlet tube, 10 mL of deionized water, 4.4 g of Span65, 2.2 g of OP-50, and 6 mL of n-butanol were added to 120 mL of white oil in sequence. The mixture was stirred at room temperature for 60 min. 0.052 mol of formaldehyde and 0.013 mol of melamine were then added in sequence. The temperature was raised to 60°C and the reaction was continued for 6 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum-dried to obtain formaldehyde-melamine polymer microspheres.
[0048] (2) Add 5g of formaldehyde-melamine polymer microspheres, 5mL of ammonia water and 30mL of 0.01mol / L C8H 12 The Mo2O8 solution was allowed to stand at 25 °C for 24 h and then freeze-dried (-60 °C, 12 Pa) for 20 h to finally obtain the polymer precursor.
[0049] (3) In a tubular furnace filled with Ar atmosphere, 50 g of polymer precursor was uniformly mixed with 2.5 g of thiourea, and the temperature was raised to 600 °C for pyrolysis for 5 h to finally obtain MoS2 / MoN / C conductive agent (the mass fraction of MoS2 was 3.3%, the mass fraction of MoN was 8.1%, and the mass fraction of C was 88.6%).
[0050] The obtained product was named conductive agent-4, and the average particle size was 6284 nm.
[0051] Example 5 (1) In a three-necked round-bottom flask equipped with a stirring rod, thermometer, and nitrogen inlet tube, 20 mL of deionized water, 7.35 g of Span 20, 2.45 g of OP-10, and 8 mL of isobutanol were added to 120 mL of kerosene in sequence. The mixture was stirred at room temperature for 30 min. 0.28 mol of formaldehyde and 0.056 mol of melamine were then added in sequence. The temperature was raised to 40°C and the reaction was continued for 12 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum-dried to obtain formaldehyde-melamine polymer microspheres.
[0052] (2) 20 g of formaldehyde-melamine polymer microspheres, 16 mL of ammonia water, and 40 mL of 0.1 mol / L (NH4)2MoO4 solution were added to 100 mL of deionized water in sequence, and the mixture was allowed to stand at 35 °C for 6 h. The mixture was then freeze-dried (-60 °C, 12 Pa) for 14 h to obtain a polymer precursor.
[0053] (3) In a tubular furnace filled with Ar atmosphere, 50 g of polymer precursor was uniformly mixed with 14.5 g of thiourea, and the temperature was raised to 700 °C for pyrolysis for 7 h to finally obtain MoS2 / MoN / C conductive agent (the mass fraction of MoS2 was 4.5%, the mass fraction of MoN was 8.2%, and the mass fraction of C was 87.3%).
[0054] The obtained product was named Conductive Agent-5, and had an average particle size of 2854 nm.
[0055] Example 6 (1) In a three-necked round-bottom flask equipped with a stirring rod, thermometer, and nitrogen inlet tube, 20 mL of deionized water, 6.72 g of Span 20, 1.68 g of Tween-870, and 7 mL of n-hexanol were added to 120 mL of kerosene in sequence. The mixture was stirred at room temperature for 45 min. 0.23 mol of formaldehyde and 0.042 mol of melamine were then added in sequence. The temperature was raised to 50°C and the reaction was continued for 7 h. After the reaction was completed, the mixture was centrifuged, washed, and vacuum-dried to obtain formaldehyde-melamine polymer microspheres.
[0056] (2) 7 g of formaldehyde-melamine polymer microspheres, 11 mL of ammonia water and 35 mL of 0.02 mol / L C8H 12 The Mo2O8 solution was allowed to stand at 33 °C for 16 h and then freeze-dried (-60 °C, 12 Pa) for 22 h to finally obtain the polymer precursor.
[0057] (3) In a tubular furnace filled with Ar atmosphere, 50 g of polymer precursor was uniformly mixed with 10 g of thiourea, and the temperature was raised to 650 °C for pyrolysis for 6 h to finally obtain MoS2 / MoN / C conductive agent (the mass fraction of MoS2 was 4.8%, the mass fraction of MoN was 8.8%, and the mass fraction of C was 86.4%).
[0058] The obtained product was named Conductive Agent-6, and the average particle size was 4219 nm.
[0059] Comparative Example 1 The TMoS2 / MoN / C conductive agent was prepared in the same manner as in Example 1, except that in step (1), "27.5 g Span60" was not added.
[0060] The obtained product was labeled D-1 and had an average particle size of 7751 nm.
[0061] Comparative Example 2 The MoS2 / MoN / C conductive agent was prepared in the same manner as in Example 1, except that in step (1), 5.5 g of Tween 20 was not added.
[0062] The obtained product was labeled D-2 and had an average particle size of 6982 nm.
[0063] Comparative Example 3 The MoS2 / MoN / C conductive agent was prepared in the same manner as in Example 1, except that in step (1), 10 mL of n-butanol was not added.
[0064] The obtained product was labeled D-3 and had an average particle size of 10.6 μm.
[0065] Comparative Example 4 The MoS2 / MoN / C conductive agent was prepared in the same manner as in Example 1, except that in step (1), the "2.64 mol formaldehyde" was changed to "0.264 mol formaldehyde".
[0066] The obtained product was labeled D-4 and had an average particle size of 1314 nm.
[0067] Comparative Example 5 The MoS2 / MoN / C conductive agent was prepared in the same manner as in Example 1, except that in step (2), the "0.08 mol / L (NH4)2MoO4 solution" was changed to "0.001 mol / L (NH4)2MoO4 solution".
[0068] The obtained product was labeled D-5 and had an average particle size of 882 nm.
[0069] Comparative Example 6 The MoS2 / MoN / C conductive agent was prepared in the same manner as in Example 1, except that in step (3), "25 g of thiourea" was not added.
[0070] The obtained product was labeled D-6 and had an average particle size of 924 nm.
[0071] Comparative Example 7 The MoS2 / MoN / C conductive agent was prepared in the same manner as in Example 1, except that in step (3), the temperature "1000°C" was changed to "100°C".
[0072] The obtained product was labeled D-7 and had an average particle size of 8457 nm.
[0073] Comparative Example 8 The MoS2 / MoN / C conductive agent was prepared in the same manner as in Example 1, except that in step (3), the “carbonization at 1000°C for 10 h” was changed to “carbonization at 1000°C for 1 h”.
[0074] The obtained product was labeled D-8 and had an average particle size of 4258 nm.
[0075] Test Example 1 Assembly method of sulfide all-solid-state battery: (1) Preparation of positive electrode materials: A conductive agent, a sulfide electrolyte LPSC, and an active material LCO were placed in an agate mortar at a weight ratio of 8:22:70 and uniformly mixed for 50 min to obtain a composite positive electrode, wherein the conductive agent was the conductive agent prepared in Examples 1 to 6 and Comparative Examples 1 to 8 or conductive carbon black (Super P).
[0076] (2) Assembly of the sulfide all-solid-state battery: 100 mg of sulfide electrolyte LPSC was added to a 10 mm diameter mold and pressed at 50 MPa for 10 min to form a solid electrolyte layer. Subsequently, 10 mg of the composite cathode was evenly spread on one side of the electrolyte layer and pressed at 200 MPa for 10 min to form a close contact with the solid electrolyte. Finally, 16 mg of Li / In anode was evenly spread on the other side of the solid electrolyte and pressed at 30 MPa for 1 min to complete the assembly of the solid-state battery.
[0077] The first-cycle coulombic efficiency and first-cycle discharge capacity (0.1C) of solid-state batteries containing different conductive carbon materials were tested. The test data are shown in Table 1.
[0078] Table 1 First cycle coulombic efficiency and discharge capacity of sulfide all-solid-state batteries with different conductive agents
[0079] It can be seen from Table 1 that the sulfide all-solid-state battery containing MoS2 / MoN / C conductive agent exhibits a higher first-cycle coulombic efficiency and discharge capacity, which are much higher than those of conductive carbon black and the conductive agents obtained in Comparative Examples 1 to 8.
[0080] Test Example 2 The discharge capacity and capacity retention rate of sulfide all-solid-state batteries with different conductive agents added after 100 cycles at a current density of 0.1C were tested. The results are shown in Table 2.
[0081] Table 2 Discharge capacity and capacity retention of sulfide all-solid-state batteries with different conductive agents after 100 cycles
[0082] It can be seen from the data in Table 2 that the sulfide all-solid-state battery containing MoS2 / MoN / C conductive agent exhibits a high capacity retention rate, which is much higher than that of conductive carbon black and the conductive agents obtained in Comparative Examples 1 to 8.
[0083] Test Example 3 The EIS impedance data of the sulfide all-solid-state battery with different conductive agents added were tested before and after 100 cycles at a current density of 0.1C. The test results are shown in Table 3.
[0084] Table 3 Impedance changes of sulfide all-solid-state batteries with different conductive agents before and after 100 cycles
[0085] As shown in Table 3, the sulfide all-solid-state batteries containing conductive carbon black and the conductive agents of Comparative Examples 1 to 8 exhibited significant post-cycle interfacial impedance changes. This is believed to be due to the presence of sulfite, which leads to interfacial instability and, in turn, inhibits electron migration, thereby deteriorating battery performance. In contrast, the sulfide all-solid-state batteries containing the MoS2 / MoN / C conductive agent of the present invention exhibited less post-cycle impedance changes, indicating that the conductive agent of the present invention does not induce chemical / electrochemical side reactions in the sulfide solid electrolyte cathode material.
[0086] Figure 2 The XPS spectrum of the positive electrode material of the sulfide all-solid-state battery containing conductive carbon black and the MoS2 / MoN / C conductive agent in Example 1 after 100 cycles, wherein a is conductive carbon black, b is MoS2 / MoN / C conductive agent, according to Figure 2 It can be seen that the composite cathode of the sulfide all-solid-state battery containing conductive carbon black produces sulfite after cycling, which inhibits interfacial ion / electron migration, while the composite cathode of the sulfide all-solid-state battery containing MoS2 / MoN / C conductive agent does not produce this byproduct. This shows that the conductive agent of the present invention is beneficial in inhibiting the formation of sulfite, a byproduct at the interface.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A method for preparing a MoS2 / MoN / C conductive agent, characterized in that: The following steps are involved: Formaldehyde, melamine, an emulsifier, an emulsifier aid, and a first solvent are mixed for polycondensation reaction to obtain formaldehyde-melamine polymer microspheres; the emulsifier comprises a first emulsifier and a second emulsifier; the first emulsifier is a Span series emulsifier, and the second emulsifier is one or more of a Tween series emulsifier and an OP series emulsifier; the molar ratio of formaldehyde to melamine is greater than or equal to 4:1; The formaldehyde-melamine polymer microspheres, ammonia water, a molybdenum salt solution and a second solvent are mixed and impregnated to obtain a polymer precursor; the concentration of the molybdenum salt solution is greater than or equal to 0.01 mol / L; The polymer precursor and thiourea are subjected to a pyrolysis reaction to obtain a MoS2 / MoN / C conductive agent; the temperature of the pyrolysis reaction is greater than or equal to 600°C, and the time is greater than or equal to 5 hours.
2. The preparation method according to claim 1, characterized in that The co-emulsifier is alcohol; the first solvent is a water-in-oil emulsion; the volume ratio of the continuous oil phase to water in the water-in-oil emulsion is (6-12):1; The ratio of the mass of the emulsifier to the volume of the first solvent is 5-15 g:100 mL; the volume ratio of the co-emulsifier to the first solvent is 2-10:100; The molar ratio of the formaldehyde to melamine is (4-12):1; the usage ratio of the melamine to the first solvent is 0.01-0.1 mol:100 mL.
3. The preparation method according to claim 1, characterized in that The temperature of the polycondensation reaction is 40-60° C., and the reaction time is 6-12 hours.
4. The preparation method according to claim 1, characterized in that The molybdenum salt in the molybdenum salt solution includes (NH4)2MoO4 and C8H 12 One or two of Mo2O8; the concentration of the molybdenum salt solution is 0.01~0.1mol / L; the second solvent is water; The volume ratio of the formaldehyde-melamine polymer microspheres to the second solvent is 5-20 g:100 mL; the volume ratio of the molybdenum salt solution to the second solvent is 30-60:100; the volume fraction of the ammonia water is 4-6%; and the volume ratio of the ammonia water to the second solvent is 5-20:
100.
5. The preparation method according to claim 1, characterized in that The immersion temperature is 25-35° C., and the immersion time is 6-24 hours.
6. The preparation method according to claim 1, characterized in that The mass ratio of the polymer precursor to thiourea is 100:5-50; the temperature of the pyrolysis reaction is 600-1000° C., the time is 5-10 hours, and the pyrolysis reaction is carried out in a protective atmosphere.
7. The MoS2 / MoN / C conductive agent prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The mass fraction of MoS2 in the MoS2 / MoN / C conductive agent is 3-5%, the mass fraction of MoN is 8-10%, and the mass fraction of C is 85-89%.
8. Use of the MoS2 / MoN / C conductive agent according to claim 7 in a sulfide all-solid-state battery.
9. A positive electrode material, characterized in that The method comprises the MoS2 / MoN / C conductive agent according to claim 7, a sulfide electrolyte and an active material.
10. A sulfide all-solid-state battery, comprising a positive electrode, a negative electrode and a sulfide solid electrolyte, characterized in that: The positive electrode is the positive electrode material according to claim 9.
Citation Information
Patent Citations
Method for preparing enhanced epoxy resin / curing agent double-wall microcapsule
CN102205225A
A preparation method of a conductive agent
CN109037685A
Nitrogen-doped molybdenum disulfide / C / three-dimensional graphene composite material
CN111106320A
Two-dimensional nitrogen-deficient / nitrogen-rich heterostructure transition metal nitride material with bidirectional catalysis function and preparation method and application thereof
CN116885179A
Solid-state battery and method for manufacturing electrode active material
US20160204466A1
Cited By
Tungsten selenide-WN Schottky junction loaded carbon material conductive agent and preparation and application thereof
CN122301182A